Use of exchange-of-knowledge method for enhancing classroom environment and students’ attitudes and achievements in Mathematics - Chapman, Flora (Curtin University, 2012)
The main aim of this study was to evaluate the relative effectiveness of the exchange-of-knowledge method (a teaching approach that offers all students in a group an equal opportunity to interact with one another on the learning tasks and to communicate their ideas in various ways) and traditional teaching methods in terms of classroom learning environment, student attitudes toward mathematics and student achievement in mathematics. Another purpose of this research was to validate suitable measures of classroom environment and students’ attitudes toward mathematics. A third aim was to investigate associations between students’ outcomes (attitudes and achievement) and their perceptions of the classroom learning environment.The sample consisted of 490 grade 6–8 students attending a middle school and 22 grade 5 students attending an elementary school in Georgia. Classroom environment was assessed using a refined version of the What Is Happening In this Class? (WIHIC) questionnaire to assess students’ perceptions of Cohesiveness/Cooperation, Teacher Support, Task Orientation, and Equity, whereas attitudes were assessed with a refined version of the Test of Science Related Attitudes (TOSRA), in which items were modified by changing the word ‘science’ to ‘mathematics’, assessing Attitude to Mathematical Inquiry and Enjoyment of Mathematics Lessons.Factor and reliability analyses revealed that a refined four-scale 25-item version of the WIHIC and a refined 17-item version of the attitude questionnaire exhibited sound factorial validity and internal consistency reliability. Also all four WIHIC scales differentiated significantly between the perceptions of students in different classrooms.Implementation of the exchange-of-knowledge method was found to have a positive impact. For the four classroom environment and two attitude scales, the control group experienced pretest-posttest changes that were both statistically nonsignificant and small in magnitude (ranging from 0.01 to 0.10 standard deviations). In contrast, the exchange-of-knowledge group experienced pretest-posttest changes on these six classroom environment and attitude scales that were statistically significant and large in magnitude (ranging from 0.63 to 3.12 standard deviations).Third, a series of simple correlation and multiple regression analyses revealed positive and statistically significant associations between students’ attitudes and the nature of the classroom environment. With the student as the unit of analysis, students’ attitudes were more positive on both scales (Attitude to Mathematical Inquiry and Enjoyment of Mathematics Lessons) in classrooms with greater Cohesiveness/Cooperation, Teacher Support, Task Orientation, and Equity.My research represents one of relatively few studies that have utilized learning environment dimensions in evaluating elementary school mathematics programs, as well as the first study to evaluate the exchange-of-knowledge method using a learning environment framework. The practical implication of my study for other mathematics educators is that the exchange-of-knowledge method has the potential to promote positive classroom environments and student attitudes among elementaryschool students.